Questionnaire survey of risk factors for recurrence of ocular inflammation in patients with uveitis after SARS-CoV-2 infection - Ma, Zonghui; Chi, Ying; Guo, Chunying; Zhang, Jing; Yang, Liu (Frontiers in Cellular and Infection Microbiology, 2024)
During the COVID-19 pandemic in China, the proportion of patients with uveitis who were infected with SARS-CoV-2 increased greatly. The impact of SARS-CoV-2 infection on patients with uveitis has not been fully described. Methods: A questionnaire on SARS-CoV-2 infection was sent to patients with uveitis to assess ocular and systemic conditions before and after infection. Chisquare analysis and multifactorial regression analysis were used to investigate the associations between each risk factor and the recurrence of uveitis after SARS-CoV-2 infection. Results: One hundred thirty-nine patients with noninfectious uveitis completed the questionnaire; 114 (82.0%) had COVID-19, and 27 (23.7%) had recurrent or exacerbated uveitis after COVID-19. There was a higher rate of recurrence or aggravation of ocular inflammation in patients who developed severe COVID-19 symptoms (severe group 8/20 vs. nonsevere group 19/94). There were significant differences in the rates of recurrence and aggravation between the two groups of patients who differed in terms of ocular inflammatory activity within 3 months prior to SARS-CoV-2 infection (χ2=10.701, P=0.001), as well as in the rates of recurrence and aggravation after cessation of systemic immunomodulatory therapy. After multifactorial regression analysis, patients with active ocular inflammation within 3 months prior to SARS-CoV-2 infection had a greater risk of recurrence or exacerbation of uveitis after P=0.002). Conclusion: The degree of ocular inflammatory activity within 3 months prior to SARS-CoV-2 infection may be a major factor influencing the recurrence or exacerbation of uveitis after infection. Interruption of medication should be minimized in patients with unstable inflammatory control.